(untitled) (Praxis Educativa, 2023)
In this paper we present our reflections from the development of a postgraduate course on teaching practices at the university, in which the contributions of the attending teachers evidenced the essential articulation of didactics with other fields of knowledge, in order to understand the problems that teaching raises in the present. Issues such as the relationship of teaching with technology, with the ways of learning of young people, affectivity as a component of teaching, attention to diversity and the working conditions of teachers are presented as topics recurring, which although they are not new, have acquired other connotations that make them more complex. This made us think in the sense of considering a "didactics from or towards the edges", focusing on the contributions of those other fields to this discipline that offer greater richness to the analysis of teaching.